الترجيح بالسياق القرآني عند ابن جُزَي الكَلبِي من خلال تفسيره التسهيل لعلوم التنزيل: دراسة تطبيقية: A Theoretical and Applied Study of Preference in the Qur’anic Context: A Case Study of al-Tashīl li Ulūm al-Tanzīl By Ibn Juzai Al-Kalbī - Abubakar Muhammad Sani; Shamsuddeen Lawan Yahya (البصيرة: مجلة الدراسات الإسلامية, 2026)
Ibn Juzayy al-Kalbi is among the exegesisors distinguished by his concise yet comprehensive approach, thorough investigation, and careful weighing of evidence in his exegesis, "Al-Tashil li-'Ulum al-Tanzil". For him, the Quranic context is a central tool for weighing interpretations when multiple interpretations exist, resolving apparent contradictions or determining the most appropriate meaning for the general or specific context. He relies heavily on circumstantial evidences to make decisions. This research aims to study his methodology in weighing interpretations based on the Quranic context, to demonstrate the extent of his attention to it, and to highlight its impact on his statements and choices in interpretations. The strength or weakness of his choices is assessed without bias. The methodology employed is inductive and analytical. One of the most prominent findings of the study is that Ibn Juzayy al-Kalbi does not merely transmit interpretations; rather, interpretive criticism is practiced, relying on the strength of the context. One of the important recommendations for researchers is to pay attention to the books of scholars of the Islamic West, especially those who have not received sufficient attention.